Taxonomic Evaluation of Monocot Flora in Karwa Pani Swamp Forest, Dehradun, Uttrakhand - Mir, Tawseef Ahmad; Dhyani, Sandeep; Jan, Muatasim (Indian Forester, 2018)
Karwa Pani Swamp forest represents a rich floral diversity. Present study deals with the enumeration of monocot flora of the swamp. This paper gives an account of 48 species of monocots belonging to 39 genera and 8 different families. Data reveals that Poaceae family of monocots is dominant family of the area with 26 species. Oplismenus compositus, Cynodon dactylon, Cyperus rotundus were found in abundance. The area is under serious threat and needs to be conserved.